Designing empathic virtual agents: manipulating animation, voice, rendering, and empathy to create persuasive agents - Parmar, Dhaval; Olafsson, Stefan; Utami, Dina; Murali, Prasanth; Bickmore, Timothy (Autonomous agents and multi-agent systems, 2022)
Designers of virtual agents have a combinatorically large space of choices for the look and behavior of their characters. We conducted two between-subjects studies to explore the systematic manipulation of animation quality, speech quality, rendering style, and simulated empathy, and its impact on perceptions of virtual agents in terms of naturalness, engagement, trust, credibility, and persuasion within a health counseling domain. In the first study, animation was varied between manually created, procedural, or no animations; voice quality was varied between recorded audio and synthetic speech; and rendering style was varied between realistic and toon-shaded. In the second study, simulated empathy of the agent was varied between no empathy, verbal-only empathic responses, and full empathy involving verbal, facial, and immediacy feedback. Results show that natural animations and recorded voice are more appropriate for the agent’s general acceptance, trust, credibility, and appropriateness for the task. However, for a brief health counseling task, animation might actually be distracting from the persuasive message, with the highest levels of persuasion found when the amount of agent animation is minimized. Further, consistent and high levels of empathy improve agent perception but may interfere with forming a trusting bond with the agent.